TYPOLOGY OF TECHNOLOGICAL LEARNING: A STUDY IN THE BAKING INDUSTRY - Araujo Vidal, Daldo Ricardo
The objective of the study was to describe the typology of technological learning in the bakery industry of the Fonseca Agribusiness and Aquaculture Center, Colombia. It was typified as descriptive, field design, non-experimental and transectional. The population was 138 key informants from bakeries in the Municipality of Guajira, using a questionnaire of 30 items, five response alternatives. Concluding that there is a high level of use of learning by use and practice, as an active source of innovations with existing equipment. Likewise, the creation of a framework of action that governs the process of technological investment for the development of learning is evident, complementing with the rest of the existing types of learning.